ANALISIS PERLINDUNGAN KONSUMEN DARI KEBOCORAN KERAHASIAAN DAN KEAMANAN DATAATAU INFORMASI DALAM TRANSAKSI JUAL BELI ONLINE (STUDI PUTUSAN NOMOR:23/PDT.SUS.BPSK/2019/ PN.CBD.) - Fernando Junio Gillardo; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2022)
This study ambitions to research how security crimes for clients in online shopping for and sellingtransactions can be very critical for improving the network's financial machine. online shopping for andpromoting transactions are basically the same as conventional shopping for and promoting andpromotions, the distinction is the media used. even as commercial commercial enterprise actors and clientsmake an settlement, both occasions are precise and highlight duties and rights that should be fulfilled. Theformula on this paper is how the duty of enterprise actors to purchasers in shopping for and promotingonline is and the way the crime of consumer security in shopping for and promoting agreements throughon-line. the usage of normative jail studies strategies. The ef ects of the assessment are, First, the task ofcommercial enterprise actors in buying and selling on-line is to provide alternative or repayment ofproblematic merchandise. secondly, prison protection for on-line purchasing customers can be provided interms of legality as stated inside the laws and guidelines governing on line buying and promoting,especially rules 19 of 2016 regarding Amendments to law range eleven of 2008 concerning facts andvirtual Transactions. and law no. - UU no. eight of 1999 regarding customer protection.